Iron deficiency anemia and megaloblastic anemia in obese patients - Arshad Mahmoud; Jaberian Sara; Pazouki Abdolreza; Riazi Sajedeh; Rangraz Maryam Aghababa; Mokhber Somayyeh (Sciendo, 2017)
Background. The association between obesity and different types of anemia remained uncertain. The present study aimed to assess the relation between obesity parameters and the occurrence of iron deficiency anemia and also megaloblastic anemia among Iranian population.